Efficacy of semduramicin against avian Coccidiosis in floor-pen trial with broilers in Venezuela - Tamasaukas, Rita; Ruiz, Héctor; Moreno, Javier; Roa, Noris (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Helvetica; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:7 0 0 0 147 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> <!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Helvetica; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:7 0 0 0 147 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Efficacy of semduramicin (25 ppm), salinomycin (60 ppm) and maduramicin (5ppm) was compared in broilers exposed to a mixture of Eimeria acervulina, E. maxima and E. tenella isolated fields, in a floor-pen trial located in Venezuela. A 5 day period was set for withdrawal feeding, containing no anticoccidial in all treatments. The weight gain of group that received 25 ppm of semduramicin was comparable to those that received 60 ppm of salinomycin or 5 ppm of maduramicin, and significantly higher compared to group of non-infected/medicated one. Feed consumption was comparable within all the experimental groups. Mortality due to coccidiosis was very low (0.78%) in non-infected/medicated group and no significant differences were observed with medicated groups. In upper, mid and cecal regions of intestine, severity of intestinal lesions was significantly lower (P < 0.05) in the group that received semduramicin than the group of non-infected/mediated chickens. As for upper region of intestine (E. acervulina), mean of damage was comparable with medicated groups. For mid gut (E. maxima) and cecal regions (E. tenella) chickens that received semduramicin had a lower range of lesion score (P â‰¤ 0.05) than those which received salinomycin. There were no significant differences in controlling damage between semduramicin and maduramicin. Â Â